2008
DOI: 10.1144/0016-76492007-076
|View full text |Cite
|
Sign up to set email alerts
|

A fluvial origin for the Neoproterozoic Morar Group, NW Scotland; implications for Torridon–Morar Group correlation and the Grenville Orogen foreland basin

Abstract: Precambrian sedimentary successions are difficult to date and correlate. In the Scottish Highlands, potential correlations between the thick, undeformed siliciclastic ‘Torridonian’ successions in the foreland of the Caledonian Orogen and the highly deformed and metamorphosed siliciclastic Moine succession within the Caledonian Orogen have long intrigued geologists. New and detailed mapping of the Neoproterozoic Altnaharra Formation (Morar Group, lowest Moine Supergroup) in Sutherland has discovered low-strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 69 publications
2
73
0
Order By: Relevance
“…origin; all are of broadly similar age and origin as the Torridon Group of the Foreland, with which they have been correlated (Krabbendam et al 2008).…”
mentioning
confidence: 88%
“…origin; all are of broadly similar age and origin as the Torridon Group of the Foreland, with which they have been correlated (Krabbendam et al 2008).…”
mentioning
confidence: 88%
“…Murchison went on to refute Nicol's interpretation strongly in a footnote in his 1858 paper (Murchison 1858b) and continued this refutation in three papers published both before (Murchison 1859) and after (Murchison & Geikie 1861a, b) the publication of Nicol's 1860 paper. (Supplied by Ryan Thigpen, based on Krabbendam et al 2008, also see Thigpen et al 2010. ) Nicol (1860) concluded that 'the line of junction, where this conformable succession is said to occur, is clearly a line of fault, everywhere indicated by proofs of fracture, contortion of the strata, and powerful igneous action'.…”
Section: Geological Observations Leading To the Highland Controversymentioning
confidence: 99%
“…Geological map of NW Scotland showing the Moine Thrust Zone, the Ben Hope Slide or Thrust, the Sgurr Beag-Naver Slide or Thrust and the Great Glen Fault (GGF). (Supplied by Ryan Thigpen, modified from Krabbendam et al 2008; also see Thigpen et al 2010. ) et al 1888) led to the structural unravelling of the Eriboll area and the subsequent closure of the Highland Controversy.…”
mentioning
confidence: 99%
“…Partly, on the basis of detrital zircon data, Cawood et al (2004) suggested an intracratonic setting. Krabbendam et al (2008), while working in the lowermost Morar Group, documented fluvial braidplain deposits similar to the Torridon Group farther west, and suggested molasse-type deposition in a foreland basin to the Grenville Orogen. Subsequent research in the stratigraphically middle part of the Morar Group (Bonsor et al 2010), showed a gradual change from fluvial to tidally influenced shallow-marine deposits.…”
mentioning
confidence: 98%
“…Nonetheless, in some orogens it has proved possible to reconstruct the main depositional environments in areas where the structural setting is relatively straightforward and exposure is of good quality. In this context, much research has been carried out on the sedimentology and basin setting of the deformed and polymetamorphic Moine Supergroup of northern Scotland (Strachan 1986;Glendinning 1988;Soper et al 1998;Bonsor & Prave 2008;Krabbendam et al 2008;Bonsor et al 2010). This is one of a number of thick early Neoproterozoic siliciclastic successions that were deposited in the North Atlantic region during and after the amalgamation of Laurentia, Baltica and Amazonia that resulted in the Grenville orogeny and the formation of the Rodinia Supercontinent (Fig 1;Hoffman 1991;Li et al 2008).…”
mentioning
confidence: 99%